2017
DOI: 10.1002/cne.24234
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cell types form the VIP amacrine cell population

Abstract: Amacrine cells are a heterogeneous group of interneurons that form microcircuits with bipolar, amacrine and ganglion cells to process visual information in the inner retina. This study has characterized the morphology, neurochemistry and major cell types of a VIP-ires-Cre amacrine cell population. VIP-tdTomato and -Confetti (Brainbow2.1) mouse lines were generated by crossing a VIP-ires-Cre line with either a Cre-dependent tdTomato or Brainbow2.1 reporter line. Retinal sections and whole-mounts were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 148 publications
(411 reference statements)
5
23
1
Order By: Relevance
“…To segregate cell types in the Vip-FlpO driver, we crossed it with the UBS-CreERT2 driver and achieved sparse labeling with a low dose of tamoxifen. The Vip-FlpO driver targeted FLPo expression in three AC types, consistent with the Cre expression pattern described in the Vip-Cre driver ( Akrouh and Kerschensteiner, 2015 ; Park et al, 2015 ; Perez de Sevilla Muller et al, 2017 ). The first type was a wide-field bistratified AC previously named VIP-1 ( Zhu et al, 2014 ; Akrouh and Kerschensteiner, 2015 ).…”
Section: Resultssupporting
confidence: 68%
“…To segregate cell types in the Vip-FlpO driver, we crossed it with the UBS-CreERT2 driver and achieved sparse labeling with a low dose of tamoxifen. The Vip-FlpO driver targeted FLPo expression in three AC types, consistent with the Cre expression pattern described in the Vip-Cre driver ( Akrouh and Kerschensteiner, 2015 ; Park et al, 2015 ; Perez de Sevilla Muller et al, 2017 ). The first type was a wide-field bistratified AC previously named VIP-1 ( Zhu et al, 2014 ; Akrouh and Kerschensteiner, 2015 ).…”
Section: Resultssupporting
confidence: 68%
“…Previous electron microscopy reconstruction of cat β cells showed that inhibitory somatic contacts may originate from a single type of GABAergic AC (47). However, we show here that mouse ooDSGCs receive input onto their somata from two or more types of ACs, one of which resembles a bistratified VIP AC (37)(38)(39) and another that resembles the type 52 AC (40). Previous electrophysiological recordings from ooDSGCs in the absence of SAC GABAergic drive revealed the presence of sustained weaker and non-direction-selective inhibitory currents (23); these currents may reflect somatic inhibition, a possibility that remains to be tested.…”
Section: Discussioncontrasting
confidence: 49%
“…Because the type or types of ACs contacting ooDSGC somata are unknown, we reconstructed the ACs that synapsed onto the ooDSGCs (n = 4 cells), using a second SBFSEM dataset (36). We found that ooDSGCs are contacted by at least two types of ACs, one with morphology resembling bistratified VIP-expressing ACs (37)(38)(39) and the other with morphology resembling the type 52 AC of Helmstaedter et al (40) (Fig. 3 F-L and SI Appendix, Fig.…”
Section: Enlarged Somatic Yfpγ2 Puncta Colocalize With Other Inhibitorymentioning
confidence: 90%
“…al, 2011), VG3 ACs (C13: VGlut3 [Slc17a8]; Haverkamp and Wässle, 2004;Johnson et al, 2004;Krishnaswamy et al, 2015); and A17 ACs (C6: Prkca (PKCα), Sdk1, Calb2 negative, Dab1-negative; Grimes et al, 2010;Puthussery and Fletcher 2007;Yamagata and Sanes, 2019). Other types expressed neuropeptides known to mark specific AC types; they include Cck (C10,C17,C18,C34; Firth et al, 2002), Vip, (C22,C26,C47; Park et al, 2015;Akrouh and Kerschensteiner, 2015;Pérez de Sevilla Müller et al, 2019), Crh (C37; Park et al, 2018) and Penk (C35,C59,C63; Chen et al, 2013). For some of these types, we were able to validate new markers, such as Car3 for VG3 cells (Figure 3B,C).…”
Section: Correspondence Between Clusters and Ac Typesmentioning
confidence: 86%